Architectural Marvels of Sikh Empire: The Gobindgarh Military Fort in Northwestern India (Journal of Carcinogenesis, 2025)
Also referred to as Bhangi Fort, Gobindgarh Fort was originally constructed in 1760 by Sardar Gujjar Singh, the chief of the Bhangi Misl. The fort is built using bricks, lime, and clay, reflecting the original construction methods of the 18th century. It was later renamed Gobindgarh Fort by Maharaja Ranjit Singh in honour of the tenth Sikh Guru, Guru Gobind Singh. Extensive renovations of the fort were carried out between 1805 and 1809 under the direction of Maharaja Ranjit Singh's two European military advisors, General Jean-Baptiste Allard and Jean-François Ventura. These modifications transformed the fort into both an artillery stronghold and the royal treasury—at one point maintaining the legendary Kohinoor diamond. The fort features a square layout, encompassing roughly 1,500 square meters, and is fortified with two massive iron-clad gates and four defensive towers at each corner. It has two main access points: the front entrance known as Nalwa Gate and the rear gate called Keller Gate. The primary entrance, also referred to as "Darwaza-e-Tope-e-Qila," included guard posts, and during Maharaja Ranjit Singh’s reign, was defended by five artillery pieces. Drawing on archaeological findings, three-dimensional analysis, and historical sources, this study interprets Gobindgarh Fort as a military-architectural hybrid that represents the strategic difficulty and adaptive strength of the Sikh Empire. It offers critical insights into heritage defence and the evolution of early modern fortification systems in South Asia.